2017
DOI: 10.1371/journal.pone.0188158
|View full text |Cite
|
Sign up to set email alerts
|

Executive function assessment in New Zealand 2-year olds born at risk of neonatal hypoglycemia

Abstract: A growing number of babies are born with perinatal risk factors that may impair later development. These children are often assessed at 2 years to help predict outcome and direct support services. Executive function is an important predictor of academic achievement and behavior, but there are limited assessments of executive function in 2-year-olds and few have been tested in at-risk populations. Therefore, we developed a battery of four age-appropriate tasks to assess executive function in 2-year-olds. At 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…Unlike in later childhood (e.g., Willoughby et al., ), but consistent with previous studies of 12‐ to 15‐month‐old children using smaller samples, we found no evidence for consistent correlations between distinct measures of EF at 14 months. Our results also mirror the weak and inconsistent correlations between EF tasks in large studies of children aged between 20 and 37 months (Ansell et al., ; Mulder et al., ). It is therefore unlikely that the lack of correlations among EF tasks in initial studies (e.g., Johansson et al., ; Miller & Marcovitch, ) was due to their small sample sizes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unlike in later childhood (e.g., Willoughby et al., ), but consistent with previous studies of 12‐ to 15‐month‐old children using smaller samples, we found no evidence for consistent correlations between distinct measures of EF at 14 months. Our results also mirror the weak and inconsistent correlations between EF tasks in large studies of children aged between 20 and 37 months (Ansell et al., ; Mulder et al., ). It is therefore unlikely that the lack of correlations among EF tasks in initial studies (e.g., Johansson et al., ; Miller & Marcovitch, ) was due to their small sample sizes.…”
Section: Discussionsupporting
confidence: 86%
“…Mirroring trends in EF research on children aged 24 months and over (e.g., Ansell, Wouldes, & Harding, ; Carlson, ; Garon, Smith, & Bryson, ; Hughes & Ensor, ; Leve et al., ; Mulder, Hoofs, Verhagen, Van der Veen, & Leseman, ; Wiebe, Espy, & Charak, ), researchers have extended the task battery approach to research on infants aged between 12 and 15 months (Johansson, Marciszko, Brocki, & Bohlin, ; Miller & Marcovitch, ; Wiebe, Lukowski, & Bauer, ). These studies have combined EF tasks previously studied in isolation to construct task batteries that include: (a) response inhibition tasks in which infants refrained from touching an attractive toy (e.g., a glittery wand; Miller & Marcovitch, ; Johansson et al., ); (b) the A‐not‐B or similar tasks (Miller & Marcovitch, ; Wiebe et al., ); (c) the Three Boxes task in which infants searched for toys hidden in three distinct locations (Miller & Marcovitch, ; Wiebe et al., ); and (d) sorting tasks in which infants learned to sort objects according to one rule and then sorted the same objects according to a different rule (Johansson et al., ; Miller & Marcovitch, ).…”
Section: Measuring Ef In the First 2 Years Of Lifementioning
confidence: 99%
“…Furthermore, our inception cohort comprised participants in a randomized clinical trial that specified glucose testing using standard methods and prospective follow-up using standardized assessments. 14,15 In contrast, some previous studies collected data retrospectively using hospital records, potentially increasing the risk of bias in assessment of exposures and outcomes. 9,19 We found that even children who had experienced brief transitional hypoglycemia and were screened and treated with the intention of maintaining blood glucose concentrations greater than or equal to 47 mg/dL are at increased risk of neurodevelopmental impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the study by Jaekel et al (2016) in which children born preterm were compared with children born full term, only the data for the latter group are used here. A borderline case is a study by Ansell et al (2017) in which the sample was composed of children who were diagnosed as being at risk for hypoglycemia during the perinatal period. However, as the study report does not indicate whether any of the children were diagnosed as diabetic at age 2 (when simple delay task performance was assessed), presumably the great majority of them were typically developing at that age.…”
Section: Selection Criteriamentioning
confidence: 99%